MEMBANGUN FILM ANIMASI CERITA RAKYAT INDONESIA - Heri Setyawan (Profetik: Jurnal Komunikasi, 2013)
Animated films is very popular in everyday society spectacle into television broadcasts over-the-air, local private television as well as public television (TVRI). Animated folklore Indonesia has tremendous potential to develop it and, While the natural beauty of Indonesia also have the potential to be explored. If these two things have combined to become the basic idea of making animated films, then it would be a very interesting artwork to watch. The Film takes the theme of folklore that had previously been known in the community as the stories in the oral form is certainly not easy to make it happen in the picture even to the stage of the animated form. An animator must use a different approach.